Evaluation of shoulder internal rotator muscle strength in baseball players with physical signs of glenohumeral joint instability. Issue 5 (26th September 2003) - Falla, D L; Hess, S; Richardson, C
Abstract : Objectives: To identify whether subjects with glenohumeral translational instability present with a strength deficit in their internal rotator musculature, and therefore to determine if general strengthening exercises are warranted for the management of this condition. Methods: Eighteen male baseball players were allocated to two groups on the basis of expert clinical evaluation of the presence (n = 8) or absence (n = 10) of shoulder translational instability. A strain gauge was used to calculate the force generated during maximal isometric internal rotation contractions in neutral shoulder rotation and 30° of internal rotation. Results: The Mann-Whitney test identified no significant difference in force production during the maximum contractions in neutral rotation between the two subject groups. In the position of 30° shoulder internal rotation, subjects with glenohumeral translational instability produced significantly greater force than the control group (p<0.05). Conclusions: High load strength testing cannot be used as a diagnostic tool to identify people with glenohumeral instability. Similarly, heavy resistance strengthening exercises for the internal rotator musculature are not warranted during rehabilitation.